Measurements and Estimation of the Extremely Low Frequency Magnetic Field of the Overhead Power Lines - Petrović, G.; Kilić, T.; Garma, T. (Elektronika ir Elektrotechnika, 2013)
Paper reports the simple model to estimate the value of the Extremely low frequency magnetic field of the overhead power line. The model is based on the application of the Biot-Savart law, considering the actual pillar head geometry and the conductors mutual position as well as their catenary shape. Additionally, it is shown that influence of the catenary on the location of the sag maxima can be neglected. The accuracy of the proposed model is verified by measuring the magnetic field of 110 kV and 400 kV overhead power line. Moreover, statistical analysis of the overhead power line current has been performed in order to determine accurate current magnitude and consecutive radiation dose. The obtained results are compared to limits directed by corresponding Croatian laws. DOI: http://dx.doi.org/10.5755/j01.eee.19.7.5159